Citra Perempuan Dalam Novel Re dan Perempuan Karya Maman Suherman: Kajian Kritik Sastra Feminis - Zahrial, Agista Refi Armadani; Israhayu, Eko Sri (Suara Bahasa, 2024)
This study is grounded in a desire to explore the portrayal of women in Indonesian literature, specifically through Maman Suherman's novel Re dan Perempuan. This novel serves as a compelling subject of study due to its complex and nuanced depiction of female characters, which reflects various issues, roles, identities, and the societal position of women. This research aims to describe and classify the image of women in the novels "Re dan Perempuan" by Maman Suherman. The study employs a descriptive analysis method using a literature review of data comprising quotes from dialogues, paragraphs, and the thoughts of characters that define the image of women in the main characters of the novel. The results of this study identify four aspects of the image of women: 1) physical aspect, 2) psychological aspect, 3) family aspect, and 4) societal aspect. In the physical aspect, "Re" is portrayed as a child undergoing puberty into adulthood, with natural beauty. In the psychological aspect, "Re" is depicted as someone with personal experiences in facing and understanding inner conflicts experienced since childhood, showcasing mature traits. In the family aspect, "Re" is illustrated as a gentle mother who showers Melur with endless affection. Melur is portrayed as a smart child, holding an MBA and a Doctorate from a university in Tokyo, Japan, demonstrating that a child born from a prostitute can also achieve high education and study abroad. In the societal aspect, "Re" is shown to open up to a man named Maman and become more connected with her child